Early clinical experience of dolutegravir in an HIV cohort in a larger teaching hospital. (October 2017) - Todd, SEJ; Rafferty, P; Walker, E; Hunter, M; Dinsmore, WW; Donnelly, CM; McCarty, EJ; Quah, SP; Emerson, CR
Dolutegravir (DTG) is the third HIV integrase inhibitor (INI) available for prescription in Belfast since July 2014. It has shown high virological efficacy in both treatment-naïve and -experienced patients. We carried out a retrospective case chart analysis of HIV-1-positive adults commenced on DTG between July 2014 and September 2015. Patients were identified from records as either treatment-naïve or antiretroviral therapy (ART) experienced. Outcomes included: (1) virological response (HIV-1 RNA viral load at 0, 4, 8 and 12 weeks), (2) immunological response (CD4+ cell count at 0, 4, 8 and 12 weeks) and (3) tolerability (side effects and discontinuation). The main exclusion criteria were patients transferring care already established on DTG from other treatment centres or inadequate follow-up information (defined as attendance at <50% of clinical and serological follow-up visits). One hundred and fifty-seven commenced DTG out of 823 patients on ART; 106 (68%) were switched to DTG from another regimen, and 51 (32%) were ART-naïve. One naïve and 14 treatment-experienced patients were excluded from the analysis due to failure to attend clinical follow-up. Analysis of HIV-1 RNA viral load (HIV-1 VL) was divided into three groups: 50 new starters, 68 suppressed at switch and 24 not suppressed at switch. New starters: Baseline median HIV-1 RNA VL 71, 259 copies/mL (19, 536Q25 −196, 413Q75 ); 73% were virally undetectable (HIV-1 RNA VL <70 copies/mL) by week 4. Switching patients: Of those with an HIV-1 RNA undetectable viral load prior to switching, two were detectable with a mean viral load of 443, 730 copies/mL after four weeks. Of the 24 patients detectable at switch (median HIV-1 VL 2212 [311Q25 −43, 467Q75 ]), 10 were detectable after four weeks. For those with a recordable viraemia, the median HIV-1 VL reduced to 376 (220Q25 −1181Q75 ). At week 12, four patients were detectable with a median VL of 12, 390 (567Q25 −52, 285Q75 ). Overall, 56 (35%) reported side effects; 40 (25%) reported either difficulty with low mood, anxiety or sleep disturbance. Sixteen (10%) discontinued DTG, with 13 (8%) due to intolerable side effects. DTG is a useful drug in naïve or switch patients. It has the potential to effectively suppress the viral load within the first four weeks of treatment and thus reduces infectiousness. Within the cohort, DTG was generally well tolerated but side effects such as low mood, anxiety and sleep disturbance were high, with 8% of patients discontinuing treatment.